Charting a new course : reinventing high school classes for the new millennium - Castro, Eric E.; Totah, Paul (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
The purpose of this book is to encourage teachers and administrators to move beyond traditional course structures and to ask them to consider designing experiential curriculum that is interdisciplinary and focused on solving real world problems. Why do this? Both authors believe that the current model of education falls short in preparing students to think creatively, to work collaboratively and to engage actively as problem solvers. An educational sea-change is needed more than ever given the problems that face our world now and that threaten to worsen in the next few decades.This book is divided into sections devoted to courses that, despite their interdisciplinary nature, we categorized into the following fields: Social Science, Literature and Composition, Computer Science, Mathematics, Art, Environment and Ecology, Engineering, Public Health, and Administration.